1986
DOI: 10.1002/cne.902470305
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal changes in the forebrain of mice following penetration by regenerating olfactory axons

Abstract: Following total, unilateral bulbectomy in neonatal mice, the olfactory sensory axons regrow from a reconstituted population of sensory neurons, cross the lamina cribrosa, and invade the spared forebrain that has leaned forward toward the anteroventral wall of the cranial cavity. The sensory axons invade several regions of the spared forebrain, at times penetrating deeply into the brain parenchyma. These axons terminate in characteristic globose structures resembling the glomeruli of the olfactory bulb. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Evidence from other studies suggests that these anomalous inputs induce some reorganization within the forebrain. Thus, sensory axon terminals form synaptic contacts on nearby multipolar neurons that extend their dendrites into these glomerular-like structures (Graziadei et al, 1978;Graziadei and Monti Graziadei, 1986), and at least some of these clusters have been observed to be associated with periglomerular-like tyrosine hydroxylase (TH)-positive neurons (Guthrie and Leon, 1989). Our tissue sections, processed for WGA-HRP and lightly counterstained with thionin, were inadequate to reveal such changes.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence from other studies suggests that these anomalous inputs induce some reorganization within the forebrain. Thus, sensory axon terminals form synaptic contacts on nearby multipolar neurons that extend their dendrites into these glomerular-like structures (Graziadei et al, 1978;Graziadei and Monti Graziadei, 1986), and at least some of these clusters have been observed to be associated with periglomerular-like tyrosine hydroxylase (TH)-positive neurons (Guthrie and Leon, 1989). Our tissue sections, processed for WGA-HRP and lightly counterstained with thionin, were inadequate to reveal such changes.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in mice have shown that olfactory epithelial axons can induce OB-like neurons in the anterior telencephalon of bulbectomized neonates (Graziadei and Monti-Graziadei, 1986). It is possible that during later development, the inductive effect of sensory axons, along with the arrival of migrating neurons from the ventral telencephalon, account for the late forming bulb-like evagination in the Fgfr1-deficient telencephalon.…”
Section: The Role Of Fgf Signaling In Ob Morphogenesismentioning
confidence: 96%
“…Following early bulbectomy, olfactory sensory axons regenerate and invade the remaining forebrain to form glomerular structures, and dendrites of forebrain neurons entering the ectopic glomeruli develop tufted structures similar to the glomerular tufts in the olfactory bulb (Graziadei and Monti Graziadei, 1986a). It is likely that the primary afferents promote the differentiation of entire primary dendrites as well as the formation of glomerular tufts (Treloar et al, 1999).…”
Section: Differentiation Of Primary and Secondary Dendritesmentioning
confidence: 98%